Strategi Guru PAI dalam Pembentukan Akhlak Peserta Didik di Era Digital: SMAN 15 Bandar Lampung - Annisa Aprilia; Chairul Amriyah; Era Octafiona (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to analyze the strategies employed by Islamic Religious Education (Pendidikan Agama Islam/PAI) teachers in shaping students’ moral character in the digital era at SMA Negeri 15 Bandar Lampung, as well as the supporting and inhibiting factors in their implementation. The research adopts a qualitative approach using a case study design. Data were collected through observation, in-depth interviews, and documentation involving PAI teachers, students, and school stakeholders as informants. Data analysis was conducted through data reduction, data display, and conclusion drawing, with data validity ensured through source and technique triangulation. The findings indicate that PAI teachers’ strategies in moral character formation are implemented through religious habituation, role modeling, the provision of advice and educational reprimands, and the limited and guided management of digital technology use. Supporting factors include a religious school culture, school policies that support character strengthening, the active role of PAI teachers, collaboration among school members, support from some parents, and religious extracurricular activities. Meanwhile, inhibiting factors include the negative influence of digital media, gadget dependency, peer influence, limited teacher supervision outside school, and diverse family backgrounds. This study concludes that the formation of students’ moral character in the digital era requires consistent strategies and synergy among schools, teachers, and families.